Diversity, polity, and the European public sphere - Sicakkan, Hakan G. (Javnost (Ljubljana), 2012)
This article proposes a conceptual and analytical framework for analysing the ongoing structuring of the European public sphere. It views the public sphere as being in a symbiotic, but non-deterministic relationship with polity forms and diversity accommodations. Operationalising the public sphere as a four-dimensional matrix of governance levels, networks, discourses, and collective actors, which takes into account the aforementioned relationship, it identifies the elements of the public sphere that should be focused on research about the European public sphere and locates the individual articles in this issue of Javnost - The Public within this matrix.
Keywords: Europe; Evropa; javna sfera; javnost; komuniciranje; communication; država; state